The Effect of Online Gambling Addiction (Slot) on Family Harmony: A Case Study of a Village Family Head Bunga Tanjung - Dhea Astri Arifina; Yusnadi; Muhammad Takwin Machmud (PT. Global Research Collaboration, 2024)
The purpose of this study is to analyze the impact of online gambling addiction (slot) on family harmony. This study was conducted with a qualitative case study approach on five heads of households in Bunga Tanjung Village who are known to have online slot gambling addiction. The results showed that the higher the online game addiction of family members, the greater the negative impact on family harmony. The main impacts of online gambling is including to reduce interaction and communication within the family, the loss of the role of husband/father as head of the family, the development of long-term conflicts, and the destruction of family welfare. The conclusion of this study is that online gambling addiction has a significant impact on the quality of family harmony. The solutions provided include the need for prevention and treatment through socialization, counseling, rehabilitation, and social support to help affected families recover from online gambling addiction.